Optimizing agronomic practices for closing rapeseed yield gaps under intensive cropping systems in China - Zhi ZHANG; Ri-huan CONG; Tao REN; Hui LI; Yun ZHU; Jian-wei LU (Journal of Integrative Agriculture, 2020)
A yield gap analysis for rapeseed (Brassica napus L.) is critical to meeting the oil demand by identifying yield potential and yield constraints. In this study, potential yield (Yp), attainable yield (Yatt), and actual yield (Yact) for winter rapeseed were determined in five different zones of China. A boundary line approach was adopted to calculate Yp, based on a large-scale field experimental database. A meta-analysis was conducted on the data obtained from 118 published studies to evaluate the effects of agronomic factors on rapeseed yield. The main results indicated that farmers only achieved 37–56% of the yield potential across the zones. The low altitude areas (L-URY) and lower reaches (LRY) of the Yangtze River Basin (YRB), China had high yield levels. The total yield gap was 1893 kg ha–1, due to the agronomic management factors, environmental factors, and socioeconomic factors. The meta-analysis showed that weed control and drainage were the best management practices to improve yields (45.6 and 35.3%, respectively), and other practices improved yields by 17.1–21.6%. Consequently, to narrow the yield gap over the short term, the study could focus on techniques that are easily implemented to farmers.